ALLERGIES DOCUMENTATION IN HMIS HISTORY OF PATIENTS ADMITTED IN GASTROENTEROLOGY AND PULMONOLOGY WARD AT LADY READING HOSPITAL, MEDICAL TEACHING INSTITUTE – PESHAWAR - Khan, Muhammad Hamza; Muhammad Khalid Shah,; Arshad Mehmood,; Usman Fazal Muhammad,; Ahmed Mustafa Khawaja,; Jamal Tauqir,; Azra Jebin,; Mah Noor Durani,; Bilal Ahmed, (Journal of Ayub Medical College Abbottabad, 2024)
Allergy is defined as an immune-mediated inflammatory response to common environmental allergens that are otherwise not harmful. Allergies included food, drug and unlisted allergies respectively. Hypersensitivity is an exaggerated immune response to antigens, manifesting from minor (atopic dermatitis and rhinitis) to dangerous manifestations such as anaphylaxis which can be life-threatening. The clinical audit aimed to confirm the proper documentation of allergies in the medical history section of the hospital management information system (HMIS) of patients admitted to the Gastroenterology and Pulmonology Ward of Lady Reading Hospital Medical Teaching Institute – Peshawar. Accurate documentation of allergies is important for patient safety and helps clinicians avoid potential allergic reactions during treatment